2006
DOI: 10.1167/iovs.04-1369
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Protect Human Retinal Pigment Epithelial Cells from Oxidative-Stress–Induced Death

Abstract: The results identify a select group of flavonoids that protect RPE cells from oxidative-stress-induced death with a high degree of potency and low toxicity. Many of these flavonoids also induce the expression of phase-2 detoxification proteins which could function to provide additional protection against oxidative stress. This select group of flavonoids and the foods that contain high levels of these compounds may have some clinical benefit for patients with retinal diseases associated with oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
207
3
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(237 citation statements)
references
References 31 publications
13
207
3
2
Order By: Relevance
“…Furthermore, EGCG exerted the protective effects against amyloid beta (Aβ) toxicity in PC12, SH-SHY5Y and mice hippocampus (Levites, Amit, Mandel, & Youdim, 2003). However, the previous study reported that EGCG did not protect against H 2 O 2 -induced oxidative stress in ARPE-19 cells (Hanneken, Lin, Johnson, & Maher, 2006), a finding which was not consistent with our study. This disparity may be due to differences in experimental procedure; in their studies ARPE-19 cells were exposed to H 2 O 2 for a period of time before adding the EGCG, cell density and concentrations of EGCG used in their experiments were lower.…”
Section: Effect Of H 2 O 2 Egcg and Caspase 3 Inhibitor On Arpe-19contrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, EGCG exerted the protective effects against amyloid beta (Aβ) toxicity in PC12, SH-SHY5Y and mice hippocampus (Levites, Amit, Mandel, & Youdim, 2003). However, the previous study reported that EGCG did not protect against H 2 O 2 -induced oxidative stress in ARPE-19 cells (Hanneken, Lin, Johnson, & Maher, 2006), a finding which was not consistent with our study. This disparity may be due to differences in experimental procedure; in their studies ARPE-19 cells were exposed to H 2 O 2 for a period of time before adding the EGCG, cell density and concentrations of EGCG used in their experiments were lower.…”
Section: Effect Of H 2 O 2 Egcg and Caspase 3 Inhibitor On Arpe-19contrasting
confidence: 99%
“…Previous studies were reported that EGCG also has protective effects against apoptosis induced by the pro-parkinsonian neurotoxin 6-hydroxydopamine (6-OHDA) in SH-SY5Y cells (Guo, Bezard, & Zhao, 2005). It has also been reported that certain flavanoids including EGCG protected RPE cells from oxidative stress induce cell death (Hanneken et al, 2006) by inducing the expression of transcription factor Nrf2 (Nuclear factor-erythroid 2-related factor-2) and phase 2 enzyme heme-oxygenase, suggesting that EGCG afforded protection via its antioxidant properties. However, a direct action of EGCG on the apoptotic pathway in ARPE-19 cells has not been demonstrated.…”
Section: Effect Of H 2 O 2 Egcg and Caspase 3 Inhibitor On Arpe-19mentioning
confidence: 99%
“…First, flavonoids can protect nerve cells from oxidative stress-induced death by both acting as a direct antioxidant and by maintaining high levels of glutathione (GSH), the major intracellular antioxidant (Ishige et al, 2001). Second, multiple studies have shown that certain flavonoids can induce the activity and expression of phase II detoxification proteins (Hanneken et al, 2006;Hou et al, 2001;Maher and Hanneken, 2005b;Maher, 2006;Myhrstad et al, 2002;Valerio et al, 2001). The phase II detoxification proteins include enzymes associated with glutathione biosynthesis and metabolism and redox sensitive proteins such as heme oxygenase 1 (HO-1) (Hayes and McLellan, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Much research in this area has focussed on stimulation of antioxidant defences via the transcription factor Nrf-2 acting at the antioxidant response element (ARE) (Li and Kong, 2009) and quercetin has been shown to stimulate this pathway (Hanneken et al, 2006). However, a number of other pathways have also been shown to be upregulated by the flavonoid in a variety of cell types (Gong et al, 2009;Jeong et al, 2009;Kampkotter et al, 2008;Triantafyllou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%